Burnout and job satisfaction among critical care nurses in Saudi Arabia and their contributing factors: A scoping review - Nawal Alzailai; Louise Barriball; Andreas Xyrichis (Wiley, 2021)
Abstract Aim Nurses working in highly demanding areas, such as intensive care units, are more likely to experience burnout and low job satisfaction than nurses working in less demanding areas. This review aims to assess the degree of well‐being of nurses working in critical care settings in Saudi Arabia by evaluating their levels of burnout and job satisfaction, as well as the factors that contribute to them. Design A scoping review. Method Seven databases were searched for published research that examined the levels and factors of burnout and job satisfaction in intensive care units nurses in the Kingdom of Saudi Arabia, as well as literature in which terminology other than "burnout" or terms related to burnout (such as "stress," "compassion fatigue" and "moral distress") were used that were conducted within Saudi Arabia. Data extraction and synthesis were performed by one reviewer and verified by a second reviewer. The present review was undertaken between January 2020 and December 2020. Results Eleven studies related to burnout and job satisfaction, and their contributing factors were identified. Evidence from this review indicated that intensive care units nurses in Saudi Arabia are suffering from moderate to high levels of burnout while experiencing only moderate levels of job satisfaction. Three categories of factors were found to be associated with burnout and nursing job satisfaction: intrapersonal, interpersonal and extra‐personal factors. The review highlights important findings for policy and nursing practice that can inform future studies and the development of burnout management strategies.